Distribution of HBV genotypes among HBV carriers in Benin:phylogenetic analysis and virological characteristics of HBV genotype E - Fujiwara, Kei (World J Gastroenterol, 2005)
AIM: To determine the distribution of Hepatitis B virus (HBV) genotypes in Benin, and to clarify the virological characteristics of the dominant genotype. METHODS: Among 500 blood donors in Benin, 21 HBsAg-positive donors were enrolled in the study. HBV genotypes were determined by enzyme immunoassay and restriction fragment length polymorphism. Complete genome sequences were determined by PCR and direct sequencing. RESULTS: HBV genotype E (HBV/E) was detected in 20/21 (95.2%), and HBV/A in 1/21 (4.8%). From the age-specific prevalence of HBeAg to anti-HBe seroconversion (SC) in 19 HBV/E subjects, SC was estimated to occur frequently in late teens in HBV/E. The comparison of four complete HBV/E genomes from HBeAg-positive subjects in this study and five HBV/E sequences recruited from the database revealed that HBV/E was distributed throughout West Africa with very low genetic diversity (nucleotide homology 96.7-99.2%). Based on the sequences in the basic core promoter (BCP) to precore region of the nine HBV/E isolates compared to those of the other genotypes, a nucleotide substitution in the BCP, G1757A, was observed in HBV/E. CONCLUSION: HBV/E is predominant in the Republic of Benin, and SC is estimated to occur in late teens in HBV/E. The specific nucleotide substitution G1757A in BCP, which might influence the virological characteristics, is observed in HBV/E.